Pendeportasian Orang Asing dalam Perspektif Hak Asasi Manusia Internasional: Ancaman Hukuman Mati dan Pemenjaraan Jangka Panjang - I Gusti Putu Anom Kresna Wardhana; Jayadi Al Amien (Student Research Journal, 2026)
Indonesia, as a sovereign state, has the absolute right to regulate the deportation of foreigners within its territory. However, in modern law, state sovereignty is no longer absolute but relative, where its implementation must refer to universal international human rights norms. This study aims to analyze the reciprocal relationship between state sovereignty and human rights enforcement in the context of the deportation of foreigners in Indonesia. The research method used is normative juridical with a legislative and conceptual approach. The results of the study indicate that state sovereignty and human rights in deportation function to limit and test each other. Sovereignty provides exclusive rights for national security through the implementation of selective policy, while international human rights law exists as a barrier so that such coercive actions do not exceed humanitarian values. In conclusion, deportation actions in Indonesia must refer to human rights norms during the deportation process. Then the state also has the absolute right to enforce immigration law in the form of deportation so as to prevent a country from becoming a refuge for criminals or international fugitives who flee to and reside in Indonesia, or carry out their criminal activities within the country.